Электрический импульсный пробой как инструмент воздействия - Алексеева Т. И. Татьяна Ивановна; Курец В. И. Валерий Исаакович; Лобанова Г. Л. Галина Леонидовна; Таракановский Э. Н. Эдуард Николаевич; Филатов Г. П. Геннадий Петрович (1996, 1996)
В фонде НТБ ТПУ отсутствует